ANALISIS STILISTIKA KUMPULAN PUISI ”DERU CAMPUR DEBU” KARYA CHARIL ANWAR - Suskandiati Suskandiati (EDU-KATA, 2019)
The purpose of this study was to describe (1) the diction, (2) prosody, and (3) the use of stylistic collection of poems "Mixed roar of Dust" by Chairil this Anwar.Penelitian using qualitative methods that are deskriptif.Objek this study were 1) structure, diction, figure of speech, prosody, stylistics and 2) the meaning or message contained in the poetry of Chairil Anwar. This research data is lines and verses that contain 1) the structure, diction, figure of speech, prosody, and style, as well as 2) the meaning and the message or thought that would be submitted by the poet. Data collection techniques are engineering documentation. Techniques and procedures analysis using three grooves: data reduction, data presentation, and drawing conclusions. The results showed that one characteristic of poetry Chairil Anwar is the powers that be in the choice of words. Every word he created capable of causing a strong imagination, and evoke a different impression, able to liven up the atmosphere, with vivid, so it emits a deep compassion for peniklmatnya. In addition, the strength in diction, characteristic lies in the poetry and literary.